Vulnerability of marine species to low oxygen under climate change - Shi, Zhiyuan (2021)
In recent decades, the ocean is becoming less oxygenated due to the combined effect of global warming and the spread of coastal eutrophication, with extensive consequences to marine ecosystems. Past mass extinctions were at least in part due to anoxic conditions in the oceans. Thus, we should be concerned about ongoing and projected declining availability of well-oxygenated habitats in the oceans. Tolerance to low oxygen is greater in smaller than larger, and less mobile than mobile taxa. The most vulnerable taxa to low oxygen are large active fish, and the least include mussels, hydrozoans, and jellyfishes. Climate change is thus likely to causes shifts in the relative abundance of species due to oxygen constraints.